2011
DOI: 10.1016/j.mce.2010.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical stem and progenitor cells: Unifying model of two proposed origins

Abstract: The origins of our understanding of the cellular and molecular mechanisms by which signaling pathways and downstream transcription factors coordinate the specification of adrenocortical cells within the adrenal gland have arisen from studies on the role of Sf1 in steroidogenesis and adrenal development initiated 20 years ago in the laboratory of Dr. Keith Parker. Adrenocortical stem/progenitor cells have been predicted to be undifferentiated and quiescent cells that remain at the periphery of the cortex until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 74 publications
0
43
0
5
Order By: Relevance
“…The use of our new Cyp11a1-Cre strain in combination with the Nr5a2 conditional allele could test this model. Cell lineage marker studies in the mouse have suggested that the definitive or adult adrenal cortical cells are derived from the foetal population and appear prior to birth (Zubair et al, 2008;Wood and Hammer, 2011). The mutant adrenal gland showed a similar dependence on SF1 for steroidogenic gene expression at E14.5 to the other tissues analysed.…”
Section: ;Nr5a2mentioning
confidence: 89%
“…The use of our new Cyp11a1-Cre strain in combination with the Nr5a2 conditional allele could test this model. Cell lineage marker studies in the mouse have suggested that the definitive or adult adrenal cortical cells are derived from the foetal population and appear prior to birth (Zubair et al, 2008;Wood and Hammer, 2011). The mutant adrenal gland showed a similar dependence on SF1 for steroidogenic gene expression at E14.5 to the other tissues analysed.…”
Section: ;Nr5a2mentioning
confidence: 89%
“…In essence, ACSCs could potentially originate from two groups of cells: either those originating from the fetal adrenal cortex or GLI1-/SHH-positive cells from the capsule/subcapsular region, both of which ultimately give rise to SF1-positive, differentiated adrenocortical cells. Wood and Hammer proposed a two-lineage unifying model suggesting the potential sources of adrenocortical stem/progenitor cells (86), but the exact mechanistic and molecular basis for the definitive relationship between the two lineages remains unclear. The regulation of adrenocortical stem/progenitor population involves a dynamic process comprising both activation and inhibition pathways, combining the exquisite orchestration of paracrine and endocrine signals to achieve an integrated homeostatic mechanism for organ maintenance.…”
Section: Adrenal Biology and Adrenocortical Stem/ Progenitor Cells (Amentioning
confidence: 99%
“…For DAX1, its inactivating mutations have been reported to be associated with X-linked adrenal congenital hypoplasia with adrenal insufficiency, a disease associated with underdevelopment of the adrenal cortex [27]. This finding is suggested, at least in part, to be attributed to DAX1 mediated regulation of adrenal progenitor cells [28]. However, the detailed mechanisms of the involvement of these two factors, which regulated the steroidogenesis in a negative manner, in the development of remodelling of subcapsular areas should be clarified by further investigations.…”
Section: Conflict Of Interestmentioning
confidence: 99%